Feasibility Study of Wind Farm Using RETScreen Model: A Case Study of Al-Razaza Site, Iraq - Resen, Ali K. (Iraqi Journal of Science, 2024)
In recent years, interest in renewable energies has increased due to their clean, renewable, and inexhaustible characteristics. Iraq faces a significant challenge in the shortage of electric power. The green economy, especially in renewable energy, has become one of the world’s main pillars, especially after the remarkable rise in greenhouse gas emissions (GHG) from fossil fuel combustion for electricity production. This study evaluates wind farm feasibility, assessing costs, revenue, and financial viability. It identifies potential hazards and difficulties, enabling developers to develop strategies to mitigate risks during project creation and operation. This paper aims to undertake a feasibility study to assess the viability of constructing a wind farm with a capacity of 340 megawatts at the Al-Razaza location in Karbala province. The study site utilized authentic data from the meteorological tower installed on the premises. The data employed spanned three years, encompassing a comprehensive and integrated dataset for the study. RETScreen, a powerful model renowned for its energy efficiency analysis and sustainable decision-making capabilities, was employed. Through the application of RETScreen, a meticulous assessment and analysis of the intricate project components were facilitated. A study of risk analysis was conducted to ascertain the impact of various parameters on the payback period of the project. The findings showed that the capacity factor of the wind farm is 22.3%, which is relatively low, the simple payback period is 10.3 years, and the energy production cost is 0.059/KWh.